2014
DOI: 10.3892/ol.2014.2274
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of four different stem cell markers in prostate cancer: High expression of NANOG in conjunction with hypoxia-inducible factor-1α expression is involved in prostate epithelial malignancy

Abstract: Cancer stem cells (CSCs) have been identified in a variety of cancer types, including prostate cancer. The aim of the present study was to evaluate the immunohistochemical expression of NANOG, octamer 4 (OCT4), cluster of differentiation 133 (CD133) and NESTIN, which are all CSC markers, and assess their function in prostate carcinogenesis. A total of 114 patients were referred to the Kanazawa Medical University Hospital (Uchinada, Japan) having presented with elevated serum prostate-specific antigen levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 54 publications
(85 reference statements)
1
29
0
Order By: Relevance
“…These pro-tumorigenic effects were associated with an upregulation of CXCR4, IGFBP5, CD133 and ALDH142. A study of CSC maker expression in 133 PCa patients has shown that all patients have positive expression of Nanog and Oct4, and a significant correlation was observed between Nanog and hypoxia-inducible factor (HIF)-1α in those patients46. These studies suggest that Nanog may be a promising biomarker for diagnosis of malignant PCa, and co-expression of Nanog and HIF-1α may predict an unfavorable prognosis since such co-expression may accelerate carcinogenesis and metastasis of PCa46.…”
Section: The Roles Of Nanog Proteins In Miscellaneous Cancersmentioning
confidence: 99%
“…These pro-tumorigenic effects were associated with an upregulation of CXCR4, IGFBP5, CD133 and ALDH142. A study of CSC maker expression in 133 PCa patients has shown that all patients have positive expression of Nanog and Oct4, and a significant correlation was observed between Nanog and hypoxia-inducible factor (HIF)-1α in those patients46. These studies suggest that Nanog may be a promising biomarker for diagnosis of malignant PCa, and co-expression of Nanog and HIF-1α may predict an unfavorable prognosis since such co-expression may accelerate carcinogenesis and metastasis of PCa46.…”
Section: The Roles Of Nanog Proteins In Miscellaneous Cancersmentioning
confidence: 99%
“…57 In contrast, nestin is recognized as a cancer stem cell marker of prostate cancer, and there are several reports on nestin as a cancer stem cell. 58,59 However, unfortunately, there is no report regarding MVD measured by using anti-nestin antibody. We emphasize here that further studies regarding the clinical significance and prognostic roles of nestin-MVD in human prostate cancer tissues are necessary.…”
Section: Nestinmentioning
confidence: 99%
“…including epithelial, mesenchymal, hematopoietic malignancies), (iii) prognostic, and (iv) mechanistic (allowing analyses of the underlying biology of the disease). Most prior reports examine whether stem cell-associated ‘factors’ are found in poorly differentiated or poor prognosis cancers [3443]. The majority of the remaining reports extend this work to investigate if a previously derived limited number of genes expressed in stem cells (a stem cell ‘signature’), if expressed in cancers, stratifies the latter by prognosis [8, 9, 4460].…”
Section: Discussionmentioning
confidence: 99%